(untitled) (Al-Qamar, 2021)
Islam has given us different principles of social reformation. Comprehensive Islamic strategy is available to address contemporary issues relating human society. Socio Economic justice is core patron of Islam to establish inclusive and peaceful society. Islamic cultural values are also best source of peace, protection and prosperity. Character building and social development totally depends on inclusive values of Islamic civilization. Islamic thought in the shape of Ijtihād is the best source to conquer contemporary issues prevailing in modern world.